2018
DOI: 10.1016/j.athoracsur.2017.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Operative Outcomes of Multiple-Arterial Versus Single-Arterial Coronary Bypass Grafting

Abstract: MABG in the United States is associated with OM comparable to SABG and increased DSWI risk with BITA-MABG. Our findings highlight the importance of surgeon and institutional experience and careful patient selection for BITA-MABG. Our short-term results should not in any way dissuade the use of MABG, given its well-established long-term survival advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
83
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 31 publications
2
83
1
2
Order By: Relevance
“…Despite of the recommendation of current guidelines to replace the SVG with the RA in patients with highdegree coronary artery stenosis [7], few surgeons were willing to choose the RA as their preferred materials; in addition to a LIMA to the left anterior descending artery (LAD), the majority of patients received the SVG. A report from STS ACSD showed that RA grafts were used in only 6.5% of all primary isolated CABG patients in the United States between 2004 to 2015, with a gradual decrease [8]. There are several reasons for its limited utilization such as few studies reporting a mean follow-up of over 10 years and possible harm to the forearm circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of the recommendation of current guidelines to replace the SVG with the RA in patients with highdegree coronary artery stenosis [7], few surgeons were willing to choose the RA as their preferred materials; in addition to a LIMA to the left anterior descending artery (LAD), the majority of patients received the SVG. A report from STS ACSD showed that RA grafts were used in only 6.5% of all primary isolated CABG patients in the United States between 2004 to 2015, with a gradual decrease [8]. There are several reasons for its limited utilization such as few studies reporting a mean follow-up of over 10 years and possible harm to the forearm circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Virtually every study to date, including the ART trial, has reported equivalent perioperative mortality with SITA versus BITA grafting. Yet recent report from the STS database has shown a significantly increased perioperative mortality with BITA versus SITA grafting 8. Whether this relates to operator experience, patient selection or some other factors will require further investigation.…”
mentioning
confidence: 98%
“…In a recent report on close to 1.5 million CABG operations, the rates of bilateral ITA and radial artery use in the United States were 4.9% and 6.5%, respectively. 3 Central considerations for low adoption of multiple arterial grafts include increased technical difficulty and concerns with greater complication rates.…”
mentioning
confidence: 99%